The Narratives of Topos: Eva Leitolf’s Deutsche Bilder – eine Spurensuche (1992–2008) and Postcards from Europe (since 2006) - Duarte, German A.; Leitolf, Eva (Review of International American Studies, 2022)
Around the turn of the century, the notion of topos (τόπος) underwent an interesting and necessary transformation. Presumably due to the popularization of digital technology, scholars started to progressively uncover the complex nature of the word by expanding on its general meaning as it pertains to the sphere of speech. This phenomenon granted to narratives some spatial characteristics, and at the same time brought into the light an old and critical relationship between text and image. In the form of a conversation, this essay deals with this critical relationship between text and image, and the way this conflictual relationship shapes social imaginaries, propaganda, and automatisms when representing social events. The essay will address these questions through an analysis of a series of pictures that had a great impact on Latin America’s social imaginary.